Analisis Margin Pemasaran Sayuran Selada Hidroponik di Stekaifarm Kelurahan Wailan Kecamatan Tomohon Utara - Tarigan, Ridho Lamindo Waraney; Pakasi, Caroline Betsi Diana; Porajouw, Oktavianus (AGRI-SOSIOEKONOMI, 2024)
This study aims to analyze the marketing margin of Stekaifarm hydroponic lettuce vegetables in Tomohon city, Wailan Village, North Tomohon District.This study uses primary data types and secondary data. Primary data obtained by themselves from observations that have been carried out directly at the research location as well as from interviews with respondents. Meanwhile, secondary data is data sourced from data that has been issued by Stekaifarm Sampling is carried out by interviewing farmers to find out other sample sources (Snowball Sampling). The number of research samples was 1 corn farmer and 3 retailers. The results of the study were analyzed using marketing margin analysis. The results of the study were analyzed using marketing margin analysis. Based on the results of the research that has been done, it can be concluded that there are only 2 levels of Stekaifarm lettuce marketing with 1 zero-level marketing pattern and 3 one-level marketing patterns. From the results of the study, the margin obtained by each institution varies in pattern I marketing level one margin obtained IDR30,000 with a profit margin of IDR19,925, pattern channel II level one IDR25,000 with profit margin IDR16,499 and pattern channel III level one IDR25,000 with profit margin of IDR23,525. The largest margin is found in the channel I pattern while the largest profit margin is in the channel III pattern. There is a difference in profit margin in each institution because the costs incurred are also different from the pattern of the first channel which has the largest marketing costs because the marketing channel is the longest.